Educational Digital Media Tools to Reformulate Activity and Object in Indigenous Science and Environmental Education - Morales, Reynaldo A. (EDU REVIEW. International Education and Learning Review / Revista Internacional de Educación y Aprendizaje, 2020)
This paper examines the functioning of and underlying assumptions about digital media in collaborative curriculum design processes in public science and environmental education, and community-designed action research learning programs. The article discusses teaching practices in US rural Northeast Wisconsin among Native Youth learning processes, from the complementation and articulation of formal and informal education to meaningful engagement and participation in science. The focus on the transformative use of digital media in science community education is intended to serve two interrelated purposes: First, it helps to address cultural-historical relations around the production of knowledge and relevant curriculums and pedagogies for rural tribal youth. Second, it intersects with the opportunities for the transferability of activity systems and action research centered around the production of mediational artifacts designed for the collective negotiation between First Nations Tribal communities and western modeled schools, institutions, workplaces, and societal roles. The transferability of this model envisions the incorporation of local actors and institutions in a deep artifact-based dialogue around epistemologies of self-determination and sustainability for Peoples who are fighting for their survival. These propositions take a new level when the transformative power of digital media shifts representations of power in historically marginalized communities, serving a larger activity of reorganizing ecologies of learning in education for culturally distinctive communities of practice.